Sistem Informasi Rekam Medis Berbasis Web Menggunakan Teknologi Sidik Jari (Studi Kasus Puskesmas Kampung Sawah) Bandar Lampung - TM zaini; M Iqbal Kadafi Nasution (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2021)
The information system at Kampung Sawah Community Health Center has several features such as patient registration, patient medical records, patient services, queues, and medical reports. Aim of this information system development is to facilitate the performance of administrators and doctors of Kampung Sawah Community Health Center in terms of searching patients’ data, storing the patient data, adding and storing the medical records, making the reports, and speeding up the data entry and identity data of the patients through fingerprint feature. This system facilitated the officials and doctors to process anywhere and the patient data was safe from physical disturbances because this system was connected to the internet.This medical record information system was built through PHP programming language supported by MySQL database. The design of this system involved the data flow diagrams. The result of this system was that the web-based information system for medical record had successfully been created and used by Kampung Sawah Community Health Center.Keywords: Information Systems, Medical Record, Web, Fingerprint